2022
DOI: 10.48550/arxiv.2204.11340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Farmer's Assistant: A Machine Learning Based Application for Agricultural Solutions

Abstract: Farmers face several challenges when growing crops like uncertain irrigation, poor soil quality, etc. Especially in India, a major fraction of farmers do not have the knowledge to select appropriate crops and fertilizers. Moreover, crop failure due to disease causes a significant loss to the farmers, as well as the consumers. While there have been recent developments in the automated detection of these diseases using Machine Learning techniques, the utilization of Deep Learning has not been fully explored. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Several studies, including those by Adams et al [5], and Ferguson et al [75], have confirmed that soybeans exhibit optimal performance in soils with pH values within this range. The order of importance of the last two predictors aligns with the observation made by Gupta et al [95] that precipitation holds greater significance than soil pH in influencing crop yield within the pH range of 5.5-7.0. This study's RF (Random Forest) model, supported by extensive data collection and comprehensive documentation of experimental P dosage sites, exhibits exceptional capabilities in generating highly personalized dose-by-dose response curves for individual diagnosed soybean fields.…”
Section: Traditional Approach To Fertilizer Recommendation Models Bas...supporting
confidence: 86%
“…Several studies, including those by Adams et al [5], and Ferguson et al [75], have confirmed that soybeans exhibit optimal performance in soils with pH values within this range. The order of importance of the last two predictors aligns with the observation made by Gupta et al [95] that precipitation holds greater significance than soil pH in influencing crop yield within the pH range of 5.5-7.0. This study's RF (Random Forest) model, supported by extensive data collection and comprehensive documentation of experimental P dosage sites, exhibits exceptional capabilities in generating highly personalized dose-by-dose response curves for individual diagnosed soybean fields.…”
Section: Traditional Approach To Fertilizer Recommendation Models Bas...supporting
confidence: 86%